Pengaruh Pengungkapan Sustainability Reporting Terhadap Kinerja Keuangan Perusahaan yang Terdaftar di Indeks Saham Syariah Indonesia Periode 2018-2021 - Tirsa Anisa Wartabone; Nilawaty Yusuf; Nurharyati Panigoro (Universitas Nusantara PGRI Kediri, 2023)
The aim of this study is to find out how the influence of disclosure of social, environmental and economic performance on financial performance is measured using the ROA profitability ratio. The research method uses descriptive quantitative. The data used is secondary data by taking figures obtained through the Indonesia Stock Exchange Website and the official Website of each company. Quantitative descriptive is used in analyzing the data. The results of the study show that disclosure of economic performance has no significant positive effect on the company’s finansial performance, as well as social performance which has no significant positive effect, while enviromental performance has a significant positive effect.